2004
DOI: 10.1007/s11745-004-1345-9
|View full text |Cite
|
Sign up to set email alerts
|

Omega‐3 PUFA of marine origin limit diet‐induced obesity in mice by reducing cellularity of adipose tissue

Abstract: Omega-3 PUFA of marine origin reduce adiposity in animals fed a high-fat diet. Our aim was to learn whether EPA and DHA could limit development of obesity and reduce cellularity of adipose tissue and whether other dietary FA could influence the effect of EPA/DHA. Weight gain induced by composite high-fat diet in C57BL/6J mice was limited when the content of EPA/DHA was increased from 1 to 12% (wt/wt) of dietary lipids. Accumulation of adipose tissue was reduced, especially of the epididymal fat. Low ratio of E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

24
241
2
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 278 publications
(272 citation statements)
references
References 35 publications
(76 reference statements)
24
241
2
5
Order By: Relevance
“…Animals and diets Experiments were performed on adult male C57BL/6J mice as described previously [1,4]. Mice were imported from the Jackson Laboratory (Bar Harbor, ME, USA) and bread at the Institute of Physiology for up to 16 generations.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Animals and diets Experiments were performed on adult male C57BL/6J mice as described previously [1,4]. Mice were imported from the Jackson Laboratory (Bar Harbor, ME, USA) and bread at the Institute of Physiology for up to 16 generations.…”
Section: Methodsmentioning
confidence: 99%
“…a composite high-fat diet, but with partial replacement of lipids by fish oil concentrate (cHF-F1 diet) such that 15% (wt/wt) of lipids was replaced by the EPA/DHA concentrate containing 6% EPA, 51% DHA, and 4 mg/g α-tocopherol as antioxidant (EPAX 1050TG; Pronova Biocare, Lysaker, Norway). Detailed analysis of fatty acid composition of the diets was performed previously [1]. When indicated, the ration was reduced by 30% (caloric restriction) compared with mice on the same type of diet but with free access to chow.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, long-chain (LC) PUFA of the n-3 series, DHA (22: 6n-3) and EPA (20: 5n-3), which are abundant in marine fish, lower TAG while increasing HDL-cholesterol levels in plasma, prevent the development of heart disease and exert anti-inflammatory properties in human Proceedings of the Nutrition Society subjects (5)(6)(7) . Studies in rats and mice fed a high-fat or lipogenic sucrose-rich diet have shown that n-3 LC PUFA counteract the development of both obesity and insulin resistance (8)(9)(10)(11)(12)(13) . Also, in human subjects n-3 LC PUFA could reduce fat accumulation and improve glucose metabolism (14)(15)(16) .…”
mentioning
confidence: 99%